Numerical modeling and simulation of multizone hydraulic fracturing using high aspect ratio interface elements - Cleto, P. [UNESP]; Maedo, M.; Rodrigues, E. [UNESP]; Camargo, M. [UNESP]; Manzoli, O. [UNESP] (My University, 2023)
Hydraulic fracturing (HF) is a reservoir stimulation technique that consists of injecting a fluid at very high pressure in a wellbore to form and propagate fractures in the reservoir. Numerical modeling and simulation can overcome the limitations associated with analytical solutions and deal with more realistic situations, such as the case of multizone hydraulic fracturing (MHF), where multiple and simultaneous fractures propagate in the reservoir. This work aims to investigate the MHF by using the Mesh Fragmentation Technique, in which high aspect ratio interface elements with suitable constitutive laws are employed to model the hydro-fracking process. The HAR-IEs are inserted between the regular elements of the finite element mesh during the pre-process. This methodology does not require the creation of new elements or a tracking algorithm to capture the fracture pattern. The fracture formation and propagation can occur freely in the domain depending only on the material properties and stress state. The application case proposed in this work investigated the simultaneous evolution of three fractures. The results showed that (i) the MFT can properly model the formation and propagation of multiple hydro-fractures and (ii) the distance between the perforations plays an important role in multizone hydraulic fracturing.